(untitled) (SCIÉNDO INGENIUM, 2022)
This article: "Creation of criminal enforcement courts as a mechanism for the effectiveness of the Peruvian prison system", is based on the fact that in Peru there are no such courts, which implies a serious situation in the execution of the sentence since There is a terrible procedural burden that is sent to the preparatory investigation courts and one-person courts, which implies in many cases requested by the inmates of the prisons that they do not receive the speed and due process that is required. With the creation of criminal enforcement courts, it will ensure the effectiveness of the Peruvian prison system. The objective was to analyze the doctrinal legal foundations, which justify the creation of the aforementioned courts. The methodology was used with a type of descriptive study in the quantitative process, the design was non-experimental - cross-sectional. It has been concluded that the proposal is feasible, since it would solve the de-overcrowding of criminal matters, the reduction of the procedural burden, the resolution of the requests of the inmates such as semi-release or conditional release, as well as enforce the right that the sentenced person of reintegration into society has once his sentence has been served.